The replacement - Yovanoff, Brenna (New York : Razorbill, 2010)
Sixteen-year-old Mackie Doyle knows that he replaced a human child when he was just an infant, and when a friend's sister disappears he goes against his family's and town's deliberate denial of the problem to confront the beings that dwell under the town, tampering with human lives.
Keywords: Changelings -- Juvenile fiction; Supernatural -- Juvenile fiction; Conformity -- Juvenile fiction; Families -- Juvenile fiction; Missing children -- Juvenile fiction; Monsters -- Juvenile fiction; Death -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Horror fiction